Flipped classroom instruction informed by output-oriented frameworks: effects on EFL learners’ engagement and idiomatic competence in Chinese higher education - Chea, Phalla; Deng, Fan (Frontiers in Education, 2026)
This study examined the effects of a mobile-mediated flipped classroom model informed by output-oriented instructional principles on English idiom learning and student engagement in Chinese higher education. A quasi-experimental design was implemented with 104 undergraduate English majors assigned to either a flipped instruction group (n = 52) or a traditional lecture-based control group (n = 52). Pre-class digital materials and collaborative in-class speaking tasks were delivered through WeChat to support idiomatic output practice. Idiomatic competence was measured using pre-/post-oral tests, while multidimensional engagement was assessed through the Higher Education Student Engagement Scale (HESES). Results showed that the flipped group achieved significantly higher idiomatic proficiency and stronger engagement than the control group. Post-test scores demonstrated a substantial achievement advantage for the flipped cohort, and engagement scores were higher across academic, cognitive, behavioral, and affective domains. The findings indicate that mobile-supported flipped instruction can enhance idiomatic learning by increasing opportunities for structured language output and interactive collaboration. The study contributes evidence for integrating mobile platforms into output-focused EFL pedagogy to support advanced linguistic development and learner engagement.